SOCIOECONOMIC AND BEHAVIORAL FACTORS CONTRIBUTING TO ANTIBIOTICS NON-ADHERENCE - Subhan Haider; Hafiz Rashid Hussain; Awais Ahmed Uttra; Mahir Ahmad khan; Muhammad Usman; Waqar ul Hassan Nadeem; Gul Zaman; Furqan Ahmed; Tahira Mumtaz (International Journal of Pharmacy & Integrated Health Sciences)
Background: Antibiotics therapy is the crucial treatment plan employed in community settings. Antibiotics effectiveness and population adherence are key causes of the efficacy of antibiotics therapy. Objectives: In this study, we pursue to explore the factors that affect patients adherence to antibiotics therapy to enhance the population adherence and to create awareness among the community related to antibiotics non-adherence. Methodology: A questionnaire survey was conducted among the university students having age range 18-40 years who had use antibiotics in the previous 6 months, data analyses were performed using SPSS version 16 by applying descriptive statistics and bivariate correlation function. Results: A total of 203 respondents participated in the survey, among them 184 participants provided complete data and were included in the study. Up to 96.7% of participants showed non-adherence to antibiotics regimen, (total adherence score <8), whereas 3.3% of participants showed good adherence, (total adherence score ≥8). Discontinuation of antibiotics due to fear of adverse effects and lack of basic knowledge about antibiotics were the important factors associated with antibiotics non-adherence. Conclusion: A range of factors was linked with non-adherence to antibiotics therapy including discontinuing treatment once the symptoms improve, changing antibiotic due to ineffectiveness, difficulty in taking prescribed dose, non-availability of pharmacy and busy work schedule.